Niche differentiation among invasive crayfish and their impacts on ecosystem structure and functioning. (16th February 2014) - Jackson, Michelle C.; Jones, Tabitha; Milligan, Maaike; Sheath, Danny; Taylor, Jeff; Ellis, Adam; England, Judy; Grey, Jonathan
Summary Many aquatic ecosystems sustain multiple invasive species and interactions among them have important implications for ecosystem structure and functioning. Here, we examine interactions among two pairs of invasive crayfish species because of their close proximity and thus chance of sympatric populations in the near future within the Thames catchment, U.K. (signal, Pacifastacus leniusculus and virile crayfish, Orconectes virilis within a river system; red swamp, Procambarus clarkii and Turkish crayfish, Astacus leptodactylus found within a suite of ponds). We address two questions: do sympatric invasive crayfish occupy a smaller niche than their allopatric counterparts due to potential resource competition? and do interactions among invasive species amplify or mitigate one another's impacts on the ecosystem? Two fully factorial mesocosm experiments (one for each crayfish pair) were used to investigate crayfish diet and their impact on benthic invertebrate community structure, benthic algal standing stock and leaf litter decomposition rates in allopatric and sympatric populations, compared with a crayfish‐free control. We used stable isotope analysis to examine crayfish diet in the mesocosms and in allopatric populations of each species in the Thames catchment. Isotopic niche width did not vary significantly between allopatric and sympatric populations of crayfish in the mesocosm experiments, and isotopic niche partitioning in all the wild populations suggests the invaders can coexist. All four species altered benthic invertebrate community structure but with differing functional effects, often mediated via trophic cascades. Red swamp crayfish predation upon snails evidently promoted benthic algal standing stock via reduction in grazing pressure. However, a trophic cascade whereby the crayfish consumed native invertebrate shredders, causing a reduction in net leaf litter decomposition, was decoupled by red swamp and signal crayfish since they consumed leaf litter directly and thus moderated the cascade to a trickle when in sympatry with Turkish or virile crayfish, respectively. Benthic invertebrate predator abundance was significantly reduced by sympatric red swamp and Turkish crayfish but not independently when in allopatry, indicating an amplified effect overall when in sympatry. Our results suggest that the combined effect of multiple invasions on the ecosystem can reflect either an additive effect of their independent impacts or an amplified effect, which is greater than the sum of their independent impacts. A lack of general pattern in their effects makes any potential management strategy more complex.